Ocena pracy doradców PRPGM dokonana przez kierowników gospodarstw a wyniki produkcyjno-ekonomiczne gospodarstw - Majewski, Janusz (Assessment of the Work of the Private Farms Dairy Development Project Advisors Made by Farms Managers and Their Production and Economic Results, 2005)
The task of agricultural advisors is to help farmers adjust to new economic conditions. The article presents actions launched by agricultural advisors within the Private Farms Dairy Development Project. The author of the article presents the opinions of farmers participating in the programme about the work of the Project's advisors in comparison with their production and economic results.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 55-60